Friction stir welding of new electronic packaging materials SiCp/Al composite with T-joint - Gao, Zeng (Array, 2018)
Using friction stir welding, the electronic container box and lid made from aluminium matrix composites with reinforcement of SiC particle (15 vol% SiCp/Al-MMCs) was welded successfully with T-joint. The temperature distribution of box during the process, mechanical property and microstructure of the joint as well as gas tightness of welded box was investigated. The experimental results indicated that the satisfactory T-joint can be obtained under appropriate friction stir welding parameters. During the welding process, the bottom center, which was used to place the electronic component, reached a quite lower temperature of 100°C. That can ensure safety of components in the box. After the welding process, the microstructure in stir zone was better than in base material due to the refining and homogeneous distribution of the SiC particles. The experimental results showed that the electronic container box after friction stir welding had gas tightness. The He-leakage rate was under 10-8 Pa•m3/s.